Pengaruh Pembiayaan Mudharabah, Pembiayaan Murabahah Dan Ijarah Terhadap Laba Perbankan Syariah Indonesia (Bank Syariah Mandiri) - Nurawwalunnisa, Nurawwalunnisa (Jurnal Ekonomi dan Bisnis, 2017)
The research aims to know the influence of mudharabah financing, murabahah financing and ijarah towards Islamic banking profits. Analytical tools used in this studi i.e., using multiple regression analysis with independent variabel mudharabah financing (X1), murabaha financing (X2) and ijarah (X3) as well the dependent variable i.e., Islamic banking profits (Y). The data on this research data for the financial statements the Bank Mandiri Syariah in period 2004-2014. The results showed that partially, mudharabah financing dan murabaha financing is variable positive significant effect against the Islamic banking profits of Bank Syariah Mandiri, ijarah while having a negative influence significantly to Islamic banking profit of Bank Syariah Mandiri. Simultaneously indicate that variable mudharabah financing, murabaha financing and ijarah simultaneous a positive effect against Islamic banking of Bank Syariah Mandiri.